Estratégia para aumento de cobertura vacinal em pacientes adultos com diabetes mellitus de um hospital universitário terciário: ensaio clínico randomizado controlado - Guerra, Giulia Limana (2022)
Diabetes mellitus is a chronic disease with a steadily rising prevalence in recent years. Immunization is an important health protection strategy in these patients. Individuals with this disease have a higher risk of fungal, viral and bacterial infections when compared to the general population. Immunization is an important health protection strategy in these patients. It is recommended that patients with diabetes mellitus have updated vaccines for influenza, pneumonia, hepatitis B and tetanus, which in Brazil are made available by the Unified Health System. This study aims to evaluate whether there is an increase in vaccination rates in patients with DM who have received guidance to update their vaccination schedules for the four vaccines mentioned above. It consisted of a randomized controlled trial between December 2018 and November 2020. The sample consisted of 228 patients from the Endocrinology outpatient clinic of the University Hospital of Santa Maria. Of these, 205 were randomized into an intervention group (n=102) and control group (n=103) and after the losses, 68 patients were analyzed in the intervention group and 71 in the control group. The intervention consisted of a telephone call guiding updating of the vaccination schedule for the evaluated diseases. It was expected to find a positive relationship between orientation and increased vaccination rate in this study. In the intervention group, there was a significant increase in the proportion of people vaccinated for the four diseases. 79.4% of the intervention group was vaccinated for influenza, and after the intervention, the number rose to 89.7% (p=0.016); 29.4% of the intervention group was vaccinated for hepatitis B, and after the intervention, the number rose to 48.5% (p=0.002); 51.5% of the intervention group was vaccinated for tetanus, and after the intervention, the number rose to 72.1% (p=0.007); 22.1% of the intervention group was vaccinated for pneumonia, and after the intervention, the number rose to 29.4% (p=0.049). In the control group, there was no significant increase in the proportion vaccinated for either disease.